The Practice of Transferring Land Ownership to a Pawn Agreement from the Perspective of Sharia Economic Law - Faizal, Liky; Tamza, Fristia Berdian (ASAS, 2023)
Receivable debt agreement, the rahin party binds the pledge guarantee in the form of a Notarial Deed of PPAT which is authorized to make a pledge agreement contract. The lien agreement is usually only carried out by binding collateral to ensure that rahin does not default on receivables given by the murtahin. However, in this agreement, the rahin party immediately promised to transfer land ownership to the murtahin party if the rahin party was unable to pay off the debt. This transfer provision, in substance, is not found in the concept of fiqh muamalah, but the rahin party only guarantees land (marhun) as collateral for debt. The focus of the problem in this study is what is the view of Islamic law on the agreement to transfer land guarantees for receivables? Meanwhile, the purpose of this study is the contract of transferring land ownership to a pawn contract from the perspective of shari'ah economic law. This research uses descriptive research method analysis with qualitative approach and literature for secondary and other data. The result of this study is that the land ownership transfer agreement that takes place in the Rahn contract is invalid, because basically the rahin only guarantees land as debt security and the transfer of land ownership has an element of imbalance between the value of debt and the value of land (marhun). In order for the Rahn transaction to be in accordance with the provisions of the Shari'a, the agreement in the repayment of the debt can be made provided that the rahin party may give the land (marhun) to the murtahin party as debt repayment, and but the murtahin party must increase the money from the remaining debt in the amount of the land priceKeywords: Pawn, Ownership, Transfer